Effect of composted sewage sludge on morpho‐physiological growth parameters, grain yield and selected functional compounds of barley. (4th August 2016) - Pasqualone, Antonella; Summo, Carmine; Centomani, Isabella; Lacolla, Giovanni; Caranfa, Gianraffaele; Cucci, Giovanna
Abstract: BACKGROUND: Several studies have evaluated the effects of composted sewage sludge on barley and found a positive influence on crop productivity. No studies have investigated the effects of composted sewage sludge on functional compounds of the caryopsis, such as phenolics and β ‐glucans. The former play a role in plant defence mechanisms and both could be influenced by variations of kernel size related to fertilization intensity. The present study aimed to evaluate the effect of different doses (3–12 mg ha −1 ) of composted sewage sludge applied alone or in combination with mineral fertilization on morpho‐physiological and yield qualitative parameters, especially phenolics and β ‐glucans contents of grains, in barley. RESULTS: Increasing fertilization rates, irrespective of fertilizer type, improved morpho‐physiological and yield parameters, whereas the phenolic compounds and the related antioxidant activity significantly decreased ( P < 0.05). The β ‐glucans and the main color indices did not show significant differences. The combined application of 6 mg ha −1 sewage sludge and nitrogen was not significantly different from mineral fertilization. Morpho‐physiological and qualitative parameters, as well as bioactive compounds, were all significantly correlated with nutrient levels, with higher r values for nitrogen. CONCLUSION: Composted sewage sludge had a similar effect compared to mineral fertilization. © 2016 Society of Chemical Industry